The heterogeneous impact of referrals on labor market outcomes - Benjamin Lester; David A. Rivers; Giorgio Topa (Federal Reserve Bank of New York, 2021)
We document a new set of facts regarding the impact of referrals on labor market outcomes. Our results highlight the importance of distinguishing between different types of referrals-those from family and friends and those from business contacts-and different occupations. Then we develop an on-the-job search model that incorporates referrals and calibrate the model to key moments in the data. The calibrated model yields new insights into the roles played by different types of referrals in the match formation process, and provides quantitative estimates of the effects of referrals on employment, earnings, output, and inequality.
Keywords: E42; E43; E44; E52; E58; 330; labor markets; referrals; networks; search theory; asymmetric information